Useful plants an introduction to economic botany - Krommenhoek, W.; de Kort, Ingrid ([United Kingdom] : ETI BioInformatics, 2005)
This cd-rom presents a survey of useful plants from the tropical, subtropical, and temperate areas
Title from container
System requirements: Windows 98/Me/XP, Pentium processor-based PC or compatible computer, 128 MB RAM, display 800x600 with 16-bit color or greater
Keywords: Botany, Economic; Botany -- economics